Design of multi-valued quaternary based analog-to-digital converter - Alam, A. H. M. Zahirul; Lawal, Wahab Adetunji; Khan, Sheroz; Rashid, Muhammad Mahbubur (Science Publications, 2009)
Problem statement: The design of multi-valued quaternary based Analog-to-Digital Converter (ADC) circuit was presented. The ADC generates multi-valued logic outputs rather than the conventional binary output system to overall reduction in circuit complexity and size. Approach: Design was implemented using pipeline ADC architecture and was simulated using model parameters based on standard 0.13 µm CMOS process. Results: Performance analysis of the design showed desirable performance parameters in terms of response, low power consumption, and a sampling rate of 10 MHz at a supply voltage of 1.3V was achieved. Conclusion/Recommendations: The ADC design was suitable for the needs of mixed-signal integrated circuit design and can be implemented as a conversion circuit for systems based on multiple-valued logic design.